Evaluación de técnica lavado de manos en estudiantes de medicina de una Universidad Pública - Maggie Anita Sotomayor Preciado; Máxima del Rocío Campoverde Ponce; Nathaly Anahí Hernández Medina; Mayerly Desiree Martínez Muñoz; Dennis Froilán Reyes Contento; Lizzie Yulieth Vásquez Vásquez; Sadia Ayling Chang Farez; Carmen Stefany Celi Romero (Salud Medicina e Innovación Journal, 2026)
Hand hygiene is the most cost-effective measure for preventing healthcare-associated infections (HAIs); however, adherence remains insufficient among health sciences students during their hospital rotations. The objective of this study was to evaluate handwashing technique among sixth-semester medical students at a public university in the province of El Oro, using direct observation tools, in order to improve safe clinical practice. A descriptive, cross-sectional study was conducted with a convenience sample of 60 students completing hospital rotations. Two instruments were used: a validated knowledge questionnaire and a direct observation checklist audit. The results showed that the majority of participants were female (63.3%) and between 18 and 21 years old (63.3%). Regarding knowledge level, a medium level was identified. The factors that most influenced non-compliance were workload overload, weak institutional supervision, and poor risk perception. Furthermore, a marked discrepancy was identified between self-reported compliance (greater than 90%) and directly observed compliance, consistent with the Hawthorne effect described in the literature. It is concluded that theoretical training does not guarantee correct practical execution; therefore, it is essential to strengthen teaching through practical workshops, continuous feedback, and structured supervision during clinical practice.